REVISITING STUDENTS’ ENTREPRENEURIAL INTENTION IN INDONESIA: A THEORY OF PLANNED BEHAVIOR APPROACH - Ambara Purusottama (Jurnal Manajemen dan Kewirausahaan, 2019)
The purpose of this study is to verify and measure entrepreneurial intentions among university students as affected by changes in the entrepreneurial environment in Indonesia. The researchers use the Theory of Planned Behavior and the concept of entrepreneurial intention to support the study. The unit of analysis is university students who are currently exposed to changes in the entrepreneurial environment. This study uses a quantitative approach with purposive sampling as the sampling technique. The questionnaire was distributed, and 631 sample responses were received from several universities. The findings show that attitude and perceived control behavior have a significant role in entrepreneurial intention. In addition, subjective norm plays no role in entrepreneurial intention